Electric Vehicle Blended Braking maximizing energy recovery while maintaining vehicle stability and maneuverability. - Boerboom, Max (My University, 2012)
The presented thesis is a part of a funded project between Saab automotive and Chalmers University of Technology. Within the organization the project is known as ‘EVBB project’ which stands for; ‘Electric Vehicle Blended Braking’. A blended brake control merges a regenerative brake system with a friction brake system. The aim is to get a better understanding regarding to what extent a regenerative brake system is capable of recovering energy and how it will affect vehicle stability and maneuverability. The variable torque and power limitations of the electric motor require a brake-by-wire system that can apply the remaining brake torque to fulfill the total brake torque demanded by the driver. Proper brake torque proportioning and the working area of the electric motor are visualized by means of brake force distribution plots. Simulations are performed for a mild parallel hybrid electric vehicle with a separate axle drive train. The drive train has a 30 [kW] electric motor mounted on the rear axle. A two track model with electric power train has been developed. The simulation results are based on this 7 DOF planar vehicle model, meaning that any pitch and roll motion of the vehicle body is excluded. The vehicle model has a closed-loop torque control, enabling velocity tracking of driving cycles. The control of lateral dynamics by means of the steering input is open-loop. A method of ‘non-linear tyre force estimation’ by means of look-up tables, based upon Pacejka’s Magic Formulas, has been used. Simulation results of two proposed control strategies show that rear wheel regenerative braking is effective. A control that initially biases the brake torque to the rear axle is able to recuperate 90% of the brake energy on the New European Driving Cycle (NEDC). Controlling the 30 [kW] regenerative brake system conforming to the ideal brake force distribution diminishes the power limitations of the electric motor. The strategy reduces the portion of regenerative brake torque but might recuperate more energy during extra urban use.
Keywords: Energi; Innovation och entreprenörskap (nyttiggörande); Transport; Farkostteknik; Energy; Innovation & Entrepreneurship; Transport; Vehicle Engineering